Myanmar Financial Sector Reforms : Policy Note - World Bank (Washington, DC : World Bank, 2022)
During Myanmar's decade of reforms, financial sector reforms were widely recognized to be a critical underpinning of Myanmar's democratization process, enabling the transition to a more egalitarian, accessible economy. Accordingly, the government developed a program of wide-ranging financial sector reform and development as described in the Financial Sector Development Strategy 2015-2020, and then supplemented and updated their approach via other strategy documents. informal providers, who could charge usury rates with little oversight. Despite significant political economy challenges and capacity constraints, since 2011 policymakers were able to carry out a substantial program of reforms to strengthen the financial sector and promote market development. However, due to the impact of COVID and the coup of February 2021, this reform agenda is at severe risk of stagnation or reversal. Progress in the modernization and accessibility of the financial sector is contingent on stability and the confidence of the public in financial institutions. Rectifying the damage to the sector under current circumstances seems especially challenging, unless there is stability and the public's confidence in the financial system is restored incrementally.